New land use planning for Tibetan villages in China based on traditional spatial patterns - Kai Xie; Yin Zhang; Wenyang Han (All Earth)
The paradox between massive rural revitalisation and cultural preservation calls for new sustainable development strategies. How to strike a balance between them has become a research hotspot especially for traditional villages in developing countries. Through data collection, field research and analogy, this article explores the spatial prototypes of mandala, Mount Meru and ‘zhai xin’ (central stronghold) concept, and points out the coupling relationship between spatial patterns and Tibetan settlements and its influences on settlement layout, architectural forms, and local customs, which includes the cultural philosophy of spatial patterns, the structure of human settlements, village layout, road network planning, and core node building complex. Taking Ge’en Tibetan Village revamping program in Aba Tibetan and Qiang County as an illustrative example, this design strategy will not only improve local residents’ living standards, but also helps to retain the cultural essence of traditional villages, thereby diving the development of tourism and other tertiary industries. Based on cultural heritage preservation, this work offers new perspectives on land use planning and architectural design for the revitalisation and sustainable development of traditional village in under-developed areas.